Effects of ammonia on hypothalamic-pituitary-ovarian axis in female rabbits - Jia Cui (Elsevier, 2021)
Background: As one of the most harmful gases in the livestock house, ammonia is recognized as an environmental stressor by Environmental Protection Agency (United States). The study aimed to explore the effect of ammonia on hypothalamic-pituitary-ovarian (HPO) axis of rabbits. A total of ninety two-month-old female IRA rabbits were randomly divided into three groups, and were kept in animal environment control rooms for four weeks at college of animal science and technology, Hebei Agricultural University (Baoding, China). The rabbits in the control group were kept under ammonia concentration of < 3 ppm. The two treatment groups were kept under ammonia concentration of 30 ppm and 50 ppm. Hypothalamus, pituitary, and ovary were collected for hematoxylin and eosin (HE) staining, immunohistochemistry, terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) and quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Serum was collected for enzyme-linked immunosorbent assay (ELISA). Results: Histopathological examination revealed that exposed to excess ammonia damaged the morphology and structure of hypothalamus, pituitary, and ovary. TUNEL assay revealed that apoptosis rate increased in hypothalamus, pituitary, and ovary. The protein expression levels of Bcl-2associated X protein (Bax) and Caspase-9 increased, while B-cell lymphoma-2 (Bcl-2) decreased, resulting in apoptosis. Moreover, the concentration of gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), and progesterone (PROG) reduced in plasma. The mRNA expression of FSH and LH in pituitary and follicle-stimulating hormone receptor (FSHR), E2, PROG in ovary as well as decreased, indicated hormone secretion disorder. Conclusions: The results indicated that ammonia exposure damaged hypothalamus, pituitary, and ovary, caused hormone secretion disorder and apoptosis.